2009
DOI: 10.1021/jp904811f
|View full text |Cite
|
Sign up to set email alerts
|

Single Nanoparticle Electrocatalysis: Effect of Monolayers on Particle and Electrode on Electron Transfer

Abstract: The electrocatalytic properties of individual single Pt nanoparticles (NPs) can be studied electrochemically by measuring the current−time (i−t) responses during single NP collisions with a noncatalytic ultramicroelectrode (UME). The Pt NPs are capped with citrate ions or a self-assembled monolayer (SAM) of alkane thiols terminated with carboxylic acid that affect the observed i−t responses. By varying the length of the SAMs or the composition of a mixed monolayer, we have studied the effect of adsorbed molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
147
1
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(164 citation statements)
references
References 15 publications
9
147
1
7
Order By: Relevance
“…However, most hot electron studies are performed at the bulk array level, which reports an ensemble average and is not sensitive to either inter-or intra-particle heterogeneities. To study particle-to-particle heterogeneity, single nanoparticle studies are required, and reports can be found in the literature in which electrochemical detection [124], surface plasmon spectroscopy [28,125,126], and single-molecule fluorescence microscopy [127][128][129][130][131][132][133] are all used to study catalytic processes at the single particle level. However, to understand the spatial localization of hot electrons in single-particle catalysis studies, super-resolution/super-localization microscopy techniques are required.…”
Section: Mapping Hot Carriers On Single Plasmonic Nanoparticles: Supementioning
confidence: 99%
“…However, most hot electron studies are performed at the bulk array level, which reports an ensemble average and is not sensitive to either inter-or intra-particle heterogeneities. To study particle-to-particle heterogeneity, single nanoparticle studies are required, and reports can be found in the literature in which electrochemical detection [124], surface plasmon spectroscopy [28,125,126], and single-molecule fluorescence microscopy [127][128][129][130][131][132][133] are all used to study catalytic processes at the single particle level. However, to understand the spatial localization of hot electrons in single-particle catalysis studies, super-resolution/super-localization microscopy techniques are required.…”
Section: Mapping Hot Carriers On Single Plasmonic Nanoparticles: Supementioning
confidence: 99%
“…This means the electron could tunnel through the 4-ATP monolayer in an outer-sphere electron transfer reaction since it is believed that the reduction of Fe(CN) 6 3À is an outersphere electron transfer reaction [28,29]. If so, the electrochemical behaviors of other outer-sphere electron transfer reactions, like the reduction of Ru(NH 3 ) 6 3 + or the oxidation of FcCH 2 OH, on a 4-ATP SAMs/Au electrode should be the same as that on the Au electrode before modification.…”
Section: àmentioning
confidence: 99%
“…According to References [22][23][24], 4-ATP molecules on the electrode are electrochemically dimerized to form 4'-mercapto-N-phenylquinone diimine (NPQD). It seems that the entire electrode is covered by NPQD molecules because the current of the oxidation of hydrazine on the modified electrode, which is believed to be an inner-sphere electron transfer reaction [28], is very small compared with the same reaction on the electrode before modification (see Figure 3c).…”
Section: àmentioning
confidence: 99%
“…A recent concept developed by Bard is that of using nanoparticle collisions at an ultramicroelectrode to determine properties such as metal nanoparticle size and the influence of capping agents on electrocatalytic reactions and electron transfer processes [50][51][52][53][54]. Since its inception many others have utilised this approach to investigate the properties of a wide range of dilute nanoparticles in solution [55][56][57][58][59][60][61][62].…”
Section: Introductionmentioning
confidence: 99%